A history of crime and the American criminal justice system - Roth, Mitchel P. (Routledge, 2019)
From customs to codes : crime and criminal justice in the ancient world -- Crime and criminal justice : English antecedents -- Crime and criminal justice in early America (1597-1740) -- Crime and criminal justice in revolutionary times (1740-1797) -- Crime and criminal justice in the new nation (1797-1834) -- Crime and criminal justice in antebellum America (1835-1857) -- Crime and criminal justice in the Civil War era (1856-1875) -- Crime and criminal justice in victorian America (1876-1901) -- Crime and criminal justice in the progressive era (1900-1919) -- Criminal justice in the crisis decades (1920-1940) -- Crime and criminal justice at midcentury (1940-1959) -- Crime and the nationalization of criminal justice (1960-1979) -- Crime and criminal justice at the end of the twentieth century (1980-1999) -- Crime and criminal justice in the age of terrorism (2000-2010) -- Crime and criminal justice in contemporary America (2011-2018) -- Conclusion -- Glossary -- Who's who in criminal justice history -- Appendices